EL ESTADO, LO TRANSNACIONAL Y LA CONSTRUCCIÓN DE COMUNIDADES CIENTÍFICAS EN LA COSTA RICA LIBERAL (1870-1930). LA CONSTRUCCIÓN DE UN “RÉGIMEN DE CIENTIFICIDAD”. - Viales Hurtado, Ronny J. (2011)
This article addresses the problem arising from the liaison between science and the concept of progress through the study of the scientific communities, the organization of the scientific field of study; the social conditions in which science develops, the significance of personal or foreign contributions; the institutionalization of science and scientific policies. To this end, the authors propose the “scientificity system” concept, which evidences the influence of local factors, such as culture, politics and economy, and their interactions that together created the unique background for the scientific development in each country. The article proposes developing several preliminary lines of interpretation concerning these scientific communities and the State, with the purpose of promoting new fields of research and areas of concern.